Towards Leveraging Digital Twin Technology in Renewable Energy Microgrids: Applications and Challenges - Li S.; Tan C.W.; Lau K.Y.; Toh C.L.; Ayob S.M.; Yang M. (Institute of Electrical and Electronics Engineers Inc., 2025)
Microgrid is one of the reliable power systems that integrates complex renewable energy sources. Along with the increasing global demand for electricity and the widespread adoption of renewable energy, the operation, management, and control of safe and reliable energy distribution have become more urgent than ever before. Microgrid digital twins provide promising solutions to these challenges. This review introduces the concepts of microgrids and digital twins along with their key features, and a conceptual framework for establishing microgrid digital twins is proposed. Explored various applications of digital twins in microgrids, including design and validation, monitoring and management, prediction, safety and fault diagnosis, education, and technical training. Finally, the challenges that microgrid digital twins may face in future studies are discussed. The review concludes that microgrid digital twins not only enhance system efficiency and reliability but also provide critical insights for future developments in energy management and operational resilience. Additionally, it offers researchers a comprehensive overview of the development and application of microgrid digital twins, further facilitating the advancement of digital twin technologies in the power system sector. ?2024 IEEE.